A Comparative Study on Narrative and Audience Experience between Chinese and Western Stage Plays - Jiang, Yuhuan (International Journal of Humanities and Social Science, 2026)
From a comprehensive cross-cultural perspective, this paper systematically compares the underlying narrative structures and the resulting audience experiences between traditional Chinese and Western stage plays. Historically, Western theatrical traditions have heavily relied on realistic, linear narration characterized by concentrated dramatic conflicts, often adhering to Aristotelian principles of unity to create a compelling illusion of reality. In stark contrast, Chinese theatrical arts frequently employ a freehand, highly virtualized, and episodic narrative style that prioritizes symbolic expression and poetic resonance over strict realism. Building upon these foundational distinctions, the paper further analyzes the profound differences in audience engagement, specifically examining viewing distance, interactive modes, and the mechanisms of emotional resonance. While Western theater often maintains a strict fourth wall that encourages psychological immersion and individual catharsis, Chinese theater traditionally fosters a more fluid, communal environment where the boundary between performer and spectator is highly permeable. The root causes of these divergent theatrical paradigms are deeply explored through the lenses of aesthetic traditions, cultural psychology, and underlying social values, ultimately revealing the essential distinctions shaped by distinct Eastern and Western cultural genes. By constructing a robust comparative framework encompassing narrative, experience, and culture, this study effectively addresses the inherent limitations of previous superficial comparisons. Ultimately, the findings provide vital theoretical support and practical insights for the creative innovation, contemporary adaptation, and effective cross-cultural communication of global theatrical arts in the modern era.